Counting on Death – Quantitative aspects of Bcl‐2 family regulation. (31st May 2018) - Hantusch, Annika; Rehm, Markus; Brunner, Thomas
Abstract : The Bcl‐2 protein family members critically regulate mitochondrial outer membrane permeabilization (MOMP), a point‐of‐no‐return in the intrinsic and extrinsic apoptosis pathways. The common view on qualitative interaction and activation patterns of the three subclasses, the BH3‐only proteins, prosurvivals, and effectors, is static and currently being revolutionized by an emerging understanding of the complex dynamic equilibria that govern cellular fate. Recent experimental evidence on protein associations with the mitochondrial outer membrane, retrotranslocation to the cytosol, and differential binding affinities in aqueous and membranous environments instigate the development of a revised model of Bcl‐2 family interplay. Likely, the dynamic processes and their respective timescales need to be taken into account to authentically understand and, by extension, to generate reliable predictions on cellular decision‐making. Here, we review the quantitative aspects of Bcl‐2 family‐regulated MOMP. In particular, we discuss affinity binding constants of protein–protein associations and velocities of post‐translational modifications, membrane (retro‐) translocations, and effector oligomerization. Moreover, we provide insights into how these kinetic and network information enable systems biological approaches, further enhancing our understanding of the complex molecular mechanisms governing MOMP. Abstract : The Bcl‐2 protein family members critically regulate mitochondrial outer membrane permeabilization (MOMP), a point‐of‐no‐return in the intrinsic and extrinsic apoptosis pathways. Here, we review the quantitative aspects of Bcl‐2 family‐regulated MOMP. We discuss how affinity binding constants of protein–protein associations and timescales of post‐translational modifications, membrane (retro‐) translocations, and effector oligomerization enhance our understanding of MOMP regulation in space and time.